Biological control of the boll weevil - Araújo, Lúcia Helena Avelino; Sobrinho, Raimundo Braga; de Almeida, Raul Porfirio; de Mesquita, Clelio Kramer (Pesquisa Agropecuaria Brasileira, 1993)
Behavioral and biological aspects of some boll weevil (Anthonomus grandis Boheman) parasitoids were studied under laboratory experiments. Parasitoidism indexes of Catolaccus grandis, Bracon spp., Catolaccus hunteri and a specie of Ichneumonidae family were 72%, 11%, 3% e 57% respectively. A specie of the Eupelmidae family was recently included in this study. These parasitoids have showed different responses to parasitize immature stages of boll weevil. High searching ability of these parasitoids for larvae inside of squares and "Parafilm M" cells was also observed.